Rancang Bangun Sistem Informasi Jasa Ekspedisi Barang Studi Kasus: PT. XYZ - Hamdani, Agus Umar; Pratiwi, Kurnia Rahayu (JURNAL NASIONAL TEKNIK ELEKTRO, 2015)
PT. XYZ is a company engaged onÂ expeditionÂ delivery services.Currently, in the data processing has still some problems, such as: Calculate of trasport expenses and commissions for driver which is often wrong, bills for customer are difficult to controlling, because it has created based on customer documents and work order has returned from delivery, Can not present about delivery information by quickly and accurate, documents are easily to lost and damaged, and takes a long time for processing and control of transaction. To solve these problems required a system that capable to handling all problems so that administrative services can be run effectively and efficiently. The purpose of this research is build a system that capable to overcome problems services in PT. XYZ. In this research, to analyze and design the proposed system use Object-Oriented Analysis and Design(OOAD metodology), programming language use Microsoft Visual .Net 2008, database use MySQL and system testing use the Black Box System.